EFEKTIVITAS PROSES PEMBELAJARAN MATA KULIAH EKONOMETRI PADA KELAS PENDIDIKAN EKONOMI 2018 UNESA DI TENGAH PANDEMI COVID-19 - Izza Milenia Ariyati; Maf Ulatul Ainiyah (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
In the era of the Covid pandemic19, the government implemented a policy on the community to remain at home. One of them is a policy to carry out learning activities at home. State University of Surabaya as a State University subject under the auspices of the ministry of education and culture must comply with the policy. However, in the process there were some shifts in achievement indicators of learning effectiveness on campus due to the Covid pandemic19. This study aims to determine the effectiveness of learning in econometrics courses in Unesa's economic education study program. This type of research is descriptive qualitative research that describes or depicts the object of research based on facts that appear or as they are. Data collection was obtained from interviews with several respondents, namely students of PE class 18 B and several documents related to the effectiveness of online lectures. Analysis of the data of this study used Nvivo 12 software. The results of the analysis that have been done that the effectiveness of lectures on econometrics courses in the pandemic era are maintained. This is because all four indicators of effectiveness are met, where the quality of learning and incentives tends to be good, while the level of teaching and time tends to be sufficient.